Moderasi Islam Pespektif Sufi: Kajian Kitab Tajul ‘Arus Karya al-Syaikh Tajuddin Ibn ‘Athaillah al-Sakandari - Harapandi Dahri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Islam as one of the divine religions carries the message of peace, harmony between people and even between God's creatures (rahmatan lil 'Ālamîn). There is no single text either al-Qur'an or al-Hadith which instructs its adherents to do the opposite, think and act radically and are anti-establishment. This problem by the previous scholars has been explained in various strokes of their thoughta. This article focuses on the thoughts of al-Shaykh Tajuddin ibn 'Athaillah al-Sakandari as one of the classical Sufism scholars who concentrate on and focus on the harmonization and moderation of Islam. By using a text and context study approach to the Kitab Tâjul 'Arus, this article finds that Islamic moderation in the Sufi perspective is seen through concepts such as al-taubah, the nature of ittibâ' al-Nabi, ahwâl al-qalb wa al-nafs, asrâr. al-Salah, as well as a lover of the world and the hereafter. Therefore, moderation in Islam is the highest value that must be maintained and carried out by every human being, so that there are no words of swearing, insults, or persecution in the name of religion, race, and group. Faith in Allah and love for the Messenger of Allah should be able to be a force in stopping all forms of injustice against everyone, even other creatures of God.Islam sebagai salah satu agama samawi membawa pesan perdamaian, keharmonian antara sesama bahkan antara makhluk Allah (rahmatan lil ‘Ālamîn). Tiada satu teks baik al-Qur’an maupun al-Hadits yang menyuruh penganutnya melakukan perkara-perkara sebaliknya, berfikir dan bertindak radikal dan anti kemapanan. Persoalan tersebut oleh para ulama’ terdahulu telah dijelaskan dalam berbagai goresan pemikirannya. Artikel ini fokus pada pemikiran al-Syaikh Tajuddin ibn ‘Athaillah al-Sakandari sebagai salah satu dari ulama tasawuf klasik yang konsen dan fokus terhadap harmonisasi dan moderasi Islam. Dengan menggunakan pendekatan kajian teks dan konteks atas Kitab Tâjul ‘Arus, artikel ini menemukan bahwa pemikiran moderasi Islam dalam perspektif sufi terlihat melalui konsep-konsep seperti al-taubah, hakikat ittibâ’ al-Nabi, ahwâl al-qalb wa al-nafs, asrâr al-Shalah, serta pencinta dunia dan akhirat. Karenanya, moderasi dalam Islam adalah nilai (value) tertinggi yang mesti dijaga dan dijalankan oleh setiap insan, sehingga tiada terdengar kata-kata umpatan, cacian, maupun persekusi atas nama agama, ras, dan juga golongan. Keyakinan akan Allah dan kecintaan kepada Rasulullah mestinya dapat menjadi kekuatan dalam memberhentikan segala bentuk ketidakadilan terhadap setiap insan bahkan pada makhluk-makhluk Tuhan yang lain.